Rev. Fac. Agron. (LUZ) Vol.38. Nº4. 2021 - Vilchez-Perozo, Jorge (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The Journal of the Faculty of Agronomy, Universidad del Zulia is a publication of the Agronomic Research Institute of the Faculty of Agronomy, Universidad del Zulia, published since 1968 and is supported by the Universidad del Zulia, in order to disseminate the results of researchers Venezuelans and other parts of the world, related to the agricultural field. The Rev. Fac. Agron. (LUZ) publishes four issues per year, with a quarterly frequency, with original and unpublished scientific articles, technical notes, review articles, quick communications, extensive summaries of congresses and scientific meetings related to the agricultural area for the consideration of the Editorial Committee. The journal publishes research products of high scientific quality and promotes the exchange of publications and scientific activity at the agricultural level, in the areas of Plant Production, Animal Production, Food Technology and Socioeconomics. The topics included in these areas are: agrosystem management, environment, agricultural biotechnology, meat science, milk science, rural development, agricultural economics, agricultural entomology, fertilizers, post-harvest physiology, plant physiology, physiology and animal reproduction, pastures and forages, animal and plant genetics and improvement, weeds, animal nutrition, plant pathology, agri-food safety, agri-food systems and soils.